Supply of alcohol to underage drinkers: Misperceptions of community norms. (December 2015) - Jones, Sandra C.; Francis, Kate L.
Abstract: Rationale: Adult approval and acceptance of alcohol use is highly correlated with underage drinking. Social norms influence young people's decisions to drink alcohol. While there is a dearth of studies to date, it is likely that social norms also influence adults' decisions to provide adolescents with alcohol. Objective: The current study explored the (in)consistencies between own and perceptions of others' views of underage drinking and the provision of alcohol to underage drinkers. Methods: Computer assisted telephone survey of 1160 adults in two communities in New South Wales, Australia. Results: Parents and community members were generally opposed to underage drinking and supply of alcohol to adolescents. Females, older respondents, and those who were parents were significantly more likely to disapprove of both underage drinking and supply of alcohol. However, across all of the behaviours, parents and non-parents alike perceived general community attitudes to be more liberal than their own. Conclusion: There is a need for community-based interventions that target parental misperceptions about the prevalence of youth drinking and the acceptability of drinking and supply of alcohol within their local community. Highlights: Most adults are opposed to youth drinking and provision of alcohol to adolescents. Parents and other adults perceive community views to be more liberal than their own. There is a need for community-level interventions to address misperception of norms.